Adverse Events Related to SARS-Cov-2 Vaccination: A Systematic Review and Meta-Analysis - Bello, Segun; Ajayi, David Taiwo; Adepoju, Akinmade; Omotosho, Temitope; Afolabi, Rotimi Felix; Gbadebo, Babatunde; Salawu, Mobolaji Modinat; Bamgboye, Eniola Adetola; Oduwole, Olabisi; Fagbamigbe, Adeniyi; Adebowale, Ayo Stephen (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Vaccination has been adopted as a key public health strategy for combating the COVID-19 pandemic. The accelerated SARS-CoV-2 vaccines’ development had limited time for extensive investigation of the adverse events. The study aimed to assess the average adverse events rates in published COVID-19 vaccination studies. Subjects and Method: The study used systematic review and meta-analysis involving studies that reported adverse events following administration of any of the approved COVID-19 vaccines in humans. A highly specific search strategy was developed and implemented in PubMed. The core search string was “(COVID-19 OR COVID OR